Analisis Faktor-Faktor Yang MempengaruhiAudit Delay(Studi Empiris Pada Perusahan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia periode 2012-2014) - Pratama, Inneke Feby, Drs. Atwal Arifin, M.Si, Ak (2016)
This study aims to analyze the affect of firm size, the quality of accounting public firm, profitibility, leverage, and audit opinion to the audit delay on manufacturing companies listed in Indonesia Stock Exchange year 2012-2014. The population in this study inlude manufacturing companies listed in Indonesia Stock Exchange year 2012-2014. The sampling technique used in this study is purposive sampling and 183 samples obtained. This study used quantitative method using secondary data obtained from direct access to www.idx.co.id. The requirement analysis test which cover normality test, multicollinearity test, heteroscedasticity test and autocorrelation test conducted before data analysis. Method of data analysis used in this research is multiple linear regression. The result of this study concludes that there are four of five factor s that may affect audit delay, which are firm size, profitibility, leverage, and audit opinion, whereas the quality of accounting public firm do not affect the audit delay.